THE IMPORTANCE OF RISK ASSESSMENT IN CAPITAL ALLOCATION - Kakhramonova Khusnora (Journals Park Publishing, 2024)
Risk assessment in capital allocation in the management of the process of capital and financial provision, risk assessment in capital allocation plays a decisive role and ensures their use. Effective financing involves planning, forecasting and monitoring cash flows to maintain liquidity and meet financial obligations.
Keywords: Risk assessment in capital allocation, Capital and financial supply process, Risk assessment in capital allocation, Correct financial forecasting, Capital decision-making, Capital structure optimization.